PEMODELAN NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN MENGGUNAKAN SEM-PLS - Ilmia, Anisa; Yulandri, Elsa (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Maximizing company value is an important factor for companies to maintain the survival of the company. This study aims to examine the determinants of factors that affect company value through dividend policy as an intervening. Researchers using PT. Telkom Indonesia as the object of research. This research approach uses quantitative descriptive, namely SEM-PLS pathway analysis to test hypotheses that have been formed. The findings of this study that financial performance and dividend policy have no effect on the company value of PT. Telkom Indonesia, Tbk. Through these findings, researchers provide information to investors that PT. Telkom Indonesia, Tbk is a stable stock and does not need to worry about company value even though there are fluctuations in stock price, dividends, and other financial performance.